2021
DOI: 10.3390/sym13061091
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Fake News Detection Method for COVID-19 Pandemic Information

Abstract: As the COVID-19 pandemic rapidly spreads across the world, regrettably, misinformation and fake news related to COVID-19 have also spread remarkably. Such misinformation has confused people. To be able to detect such COVID-19 misinformation, an effective detection method should be applied to obtain more accurate information. This will help people and researchers easily differentiate between true and fake news. The objective of this research was to introduce an enhanced evolutionary detection approach to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Al-Ahmad et al [ 116 ], suggested a powerful approach for detecting misleading news. This approach employs kNN–BSSA, kNN–BPSO, kNN–BGA with feature selection, and the standard kNN models to reduce the number of symmetrical features.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Al-Ahmad et al [ 116 ], suggested a powerful approach for detecting misleading news. This approach employs kNN–BSSA, kNN–BPSO, kNN–BGA with feature selection, and the standard kNN models to reduce the number of symmetrical features.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most effective way to obtain such an estimate is numerical analysis based on random search for optimal parameters of the management strategy. One of the implementations of random search is evolutionary modeling, which has found wide application in numerical optimization problems [23][24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…Fake news starting with shocking headlines can lead to serious results since infections, in particular, are directly associated with human lives [13]. Research on detecting fake news on COVID-19 is actively conducted overseas since there is an ample amount of usable data amid the COVID-19 outbreak [14,15]. However, research is less actively conducted in Korea due to a lack of useful data.…”
Section: Introductionmentioning
confidence: 99%